TINDAK LANJUT PUTUSAN MAHKAMAH KONSTITUSI OLEH DPR RI - Lumbuun, Topane Gayus (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2009)
One of the power of the Constitutional Court (MK) is to examinethe laws under the Constitution regarding its substance or thecontents of the laws as well as procedural aspect of the lawmaking. The MK power can be categorized as a negativelegislation from the perspective of legislation of laws, becauseit can revoke the laws if such laws are in contradiction with1945 Indonesian Constitution. Therefore, the MK judgmentrevoking the norms in contradiction to the 1945 IndonesiaConstitution is binding and final. With such final and bindingin nature, there is no legal appeal which can be done tochallenge of MK judgment’s. Follow up of such judgment, isthe positive legislation held jointly by the President and theDPR. Then, the problem is that MK judgments do notautomatically receive response from DPR for its amendment orits revision as mandated by MK. Practically and in itsimplementation, DPR has not implemented the MK judgmentand as such the execution of MK’s judgment is not as easy as itseems. There are two important factors for DPR in conductinglegislative review. The first relates to the controversies containedin thse substance of MK’s judgment . Secondly relates to themechanism and submission structure of draft laws to DPR whichshould be planned and integrated scheme of national legislationprogrammes.